The LEGO movie : junior novel - Howard, Kate.; Hageman, Dan.; Hageman, Kevin; Lord, Phil, 1977-; Miller, Chris, 1975- (New York, NY : Scholastic Inc., 2014)
"Emmet, an ordinary LEGO Minifigure, is mistakenly thought to be an extraordinary Master Builder and he is recruited to join a quest to stop an evil tyrant (Lord Business) from gluing the universe together, thus destroying creativity. Now Emmet and his friend Lucy need to go on a quest through various LEGO lands to save the world"--Provided by publisher.
5.8
3-6.
3-6
Keywords: Good and evil -- Juvenile fiction; Adventure and adventurers -- Fiction; Good and evil -- Fiction; Adventure fiction; Good and evil -- Fiction; Movie novels; Adventure fiction; Movie novels